Child Abuse and Neglect, Social Support, and Psychopathology in Adulthood: A Prospective Investigation - Sperry, Debbie M. (2013)
OBJECTIVE: To determine whether child abuse and neglect predicts low levels of social support in middle adulthood and understand whether social support acts to mediate or moderate the relationship between childhood abuse and neglect and subsequent outcomes (anxiety, depression, and illicit drug use). METHOD: Using data from a prospective cohort design study, children with documented histories of physical and sexual abuse and neglect (ages 0–11) during the years 1967 through 1971 and a matched control group were followed up and interviewed in adulthood. Social support was assessed at mean age 39.5, and anxiety, depression, and illicit drug use at mean age 41.2. RESULTS: Adjusting for age, sex, and race, individuals with documented histories of child abuse and neglect reported significantly lower levels of social support in adulthood [total (p<.001), appraisal (p<.001), belonging (p<.001), tangible (p<.001), and self-esteem support (p<.01)] than controls. Adjusting for age, sex, race, and prior psychiatric diagnosis, social support mediated the relationship between child abuse and neglect and anxiety and depression in adulthood. Four gender by social support interactions and one three-way [group (abuse/neglect versus control) × tangible social support × gender) interaction moderated levels of anxiety and depression, particularly for males who were more strongly affected by high levels of social support. CONCLUSIONS: Social support plays a significant role in mediating and moderating some long term consequences of childhood maltreatment. Efforts to better understand the timing and mechanisms involved in these relationships are needed to guide preventive interventions and treatment.